2015
DOI: 10.1039/c5mt00226e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of platinum based on laser ablation-inductively coupled plasma-mass spectrometry to investigate toxic side effects of cisplatin

Abstract: This work presents a quantitative bioimaging method for platinum based on laser ablation-inductively coupled plasma-mass spectrometry and its application for a biomedical study concerning toxic side effects of cisplatin. To trace the histopathology back to cisplatin, platinum was localized and quantified in major functional units of testicle, cochlea, kidney, nerve and brain sections from cisplatin treated mice. The direct consideration of the histology enables precise interpretation of the Pt images and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
1
26
1
Order By: Relevance
“…The glomerulus at the right side of the image corresponds to the dark blue zone, indicating very low cisplatin accumulation, which is in agreement with the findings of Moreno-Gordaliza et al [36], who indicated cisplatin was absent in glomeruli. In contrast to our results based on a single dose administration, Köppen et al [35] reported the presence of significant amounts of cisplatin in the glomeruli of mice kidneys after cisplatin administration of eight doses of …”
Section: Articlecontrasting
confidence: 55%
See 1 more Smart Citation
“…The glomerulus at the right side of the image corresponds to the dark blue zone, indicating very low cisplatin accumulation, which is in agreement with the findings of Moreno-Gordaliza et al [36], who indicated cisplatin was absent in glomeruli. In contrast to our results based on a single dose administration, Köppen et al [35] reported the presence of significant amounts of cisplatin in the glomeruli of mice kidneys after cisplatin administration of eight doses of …”
Section: Articlecontrasting
confidence: 55%
“…Different tubular structures can be recognized in the Pt distribution map and as expected, cisplatin is mainly present in the epithelial cells of proximal and distal tubules. Previous studies [35,36] on this topic also indicate the accumulation of cisplatin in tubular epithelial cells. The lumens of these tubular segments are low in cisplatin.…”
Section: Articlementioning
confidence: 94%
“…In addition, recent studies3537 using cancer cell lines, Hep3B, HepJ5, ES-2, SKOV-3, OVCAR-3, MCF-7, revealed significant decreases in cell viability after DXR exposure. On the other hand, the same degree of sensitivity from the 2D system did not translate to a 3D culture system, resulting in higher IC50 values than the 2D system 38.…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, the same degree of sensitivity from the 2D system did not translate to a 3D culture system, resulting in higher IC50 values than the 2D system 38. Greatly reduced cell viabilities from DXR treatments were observed from uterus/endometrium cancer (KLE) and colon carcinoma (HCT116), osteogenic sarcoma (Saos-2), and bone osteosarcoma (HOS), which were cultured in 3D system 3335,39. In addition, a significant effect of DXR towards 3D-spheroid forms of Ishikawa human endometrial cancer cells (RL95-2) was revealed by measuring cell viability 40.…”
Section: Introductionmentioning
confidence: 99%
“…Sections of explants treated with cisplatin were subjected to Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to produce elemental maps showing the spatial distribution of platinum in tissue sections (25). The method is described in Supplementary Fig.…”
Section: Laser Ablation Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%